On cellular indecomposable property of semi-Fredholm operators - Cheng, Guozheng; Fang, Xiang (My University, 2012)
In this paper we prove that an operator with the cellular indecomposable property has no singular points in the semi-Fredholm domain. Besides its own interests, this fills a gap in [3]. Our proof relies on the 4 × 4 matrix model of semi-Fredholm operators [2].
Keywords: Cellular indecomposable property; Semi-Fredholm operator; Singular points